Ecosystem health report cards: An overview of frameworks and analytical methodologies. (June 2020) - Logan, Murray; Hu, Ziyuan; Brinkman, Richard; Sun, Song; Sun, Xiaoxia; Schaffelke, Britta
Highlights: Overview of the report card framework. Overview of indicator selection. Descriptions of different index formulations. Descriptions of index aggregation methodologies. Abstract: Ecosystem health report cards have become increasingly more important tools for communicating environmental state and assessing progress towards management goals. We provide an overview of the major analytical methods underpinning the translation of observed data into robust health indices. In particular, we outline the process of indicator selection, illustrate a variety of index metrics and describe index aggregation with consideration for weighting and the propagation of uncertainty.